2013
DOI: 10.1111/acel.12075
|View full text |Cite
|
Sign up to set email alerts
|

Metformin inhibits the senescence‐associated secretory phenotype by interfering with IKK/NF‐κB activation

Abstract: SummaryWe show that the antidiabetic drug metformin inhibits the expression of genes coding for multiple inflammatory cytokines seen during cellular senescence. Conditioned medium (CM) from senescent cells stimulates the growth of prostate cancer cells but treatment of senescent cells with metformin inhibited this effect. Bioinformatic analysis of genes downregulated by metformin suggests that the drug blocks the activity of the transcription factor NF-jB. In agreement, metformin prevented the translocation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
338
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 481 publications
(348 citation statements)
references
References 45 publications
7
338
0
3
Order By: Relevance
“…We have observed strong experimental evidence that metformin can act to suppress inflammation associated with senescence [40], and there is also convincing evidence from in vivo and in vitro models that the drug suppresses cancer-related inflammation [41]. In both cases, NF-κB activation is reduced, with concomitant reductions in secretion of inflammatory cytokines.…”
Section: Metformin and The Immune Systemmentioning
confidence: 88%
See 2 more Smart Citations
“…We have observed strong experimental evidence that metformin can act to suppress inflammation associated with senescence [40], and there is also convincing evidence from in vivo and in vitro models that the drug suppresses cancer-related inflammation [41]. In both cases, NF-κB activation is reduced, with concomitant reductions in secretion of inflammatory cytokines.…”
Section: Metformin and The Immune Systemmentioning
confidence: 88%
“…Although no detailed clinical studies examining influences of metformin on more subtle aspects of immune function have been carried out, laboratory studies [34][35][36][37][38][39][40][41][42][43][44][45] have provided considerable evidence for a variety of immunomodulatory effects.…”
Section: Metformin and The Immune Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, partial suppression of the SASP seems to be a reasonable option, particularly when short-term alleviation of agerelated dysfunction might be indicated. Several drugs, including glucocorticoids (57), metformin (58), and rapamycin (59), have been found to inhibit the SASP. Inhibition of the JAK/STAT pathway appears to be a viable option for the following reasons.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, approaches to separate the beneficial tumor-suppressive growth arrest of senescence from the deleterious secretion of the SASP would be of significant clinical value (Coppe et al 2010;Munoz-Espin and Serrano 2014;van Deursen 2014). Indeed, recent studies have shown that the mechanism of the anti-aging and anti-cancer effects of the diabetes medication metformin may be through SASP inhibition (Algire et al 2012;Moiseeva et al 2013).…”
mentioning
confidence: 99%